2016
DOI: 10.1093/brain/aww031
|View full text |Cite
|
Sign up to set email alerts
|

Glial and axonal changes in systemic lupus erythematosus measured with diffusion of intracellular metabolites

Abstract: Systemic lupus erythematosus is an inflammatory autoimmune disease with multi-organ involvement. Central nervous system involvement in systemic lupus erythematosus is common and results in several neurological and psychiatric symptoms that are poorly linked to standard magnetic resonance imaging outcome. Magnetic resonance imaging methods sensitive to tissue microstructural changes, such as diffusion tensor imaging and magnetization transfer imaging, show some correlation with neuropsychiatric systemic lupus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 48 publications
4
76
0
3
Order By: Relevance
“…As was previously mentioned, the cytosolic diffusion coefficient of NAA is a good candidate for a putative marker for intracellular damage such as axonopathy in MS, but this role can be extended to other neurodegenerative disorders, such as tauopathy in AD, where intraneuronal pathological changes are caused by hyperphosphorylation of the tau protein, which is responsible for keeping the integrity of microtubules (152)(153)(154). In a combined DTI -DW-MRS study of patients with neuropsychiatric systemic lupus erythematosus (NPSLE), an increase in the diffusion coefficient of tCho was observed in correlation with neuropsychiatric symptoms and with the SLE disease activity index (SLEDAI), which scales with inflammatory state (155). This points to the possibility that tCho's ADC is modulated by inflammation and reflects glial reactivity in response to inflammation.…”
Section: Multivoxel Dw-mrs and Dw-mrsimentioning
confidence: 99%
“…As was previously mentioned, the cytosolic diffusion coefficient of NAA is a good candidate for a putative marker for intracellular damage such as axonopathy in MS, but this role can be extended to other neurodegenerative disorders, such as tauopathy in AD, where intraneuronal pathological changes are caused by hyperphosphorylation of the tau protein, which is responsible for keeping the integrity of microtubules (152)(153)(154). In a combined DTI -DW-MRS study of patients with neuropsychiatric systemic lupus erythematosus (NPSLE), an increase in the diffusion coefficient of tCho was observed in correlation with neuropsychiatric symptoms and with the SLE disease activity index (SLEDAI), which scales with inflammatory state (155). This points to the possibility that tCho's ADC is modulated by inflammation and reflects glial reactivity in response to inflammation.…”
Section: Multivoxel Dw-mrs and Dw-mrsimentioning
confidence: 99%
“…Changes in endogenous metabolite apparent diffusivity (ADC) have already been detected in pathologies. Alterations in the diffusion of metabolites are observed after global ischemia (4)(5)(6)(7)(8)(9), in multiple sclerosis (10), in brain tumor (11)(12)(13), and in lupus erythematosus (14). Although alterations of intracellular diffusion during brain pathologies are often thought to be associated with cell structural damage, the influence of various parameters (eg, viscosity, molecular crowding, cell size, geometry) on DW-MRS measurement is still unclear, and the interpretation of experimental data remains complex.…”
Section: Introductionmentioning
confidence: 99%
“…tNAA diffusion properties in white matter are therefore solely dictated by the structural properties of intra-axonal components and by the properties of the intra-axonal medium, thus providing a specific marker to the axonal contribution to WM degeneration. Soluble Choline compounds are located mainly in glial cells (Choi, et al, 2007,Le Belle, et al, 2002,Urenjak, et al, 1993 and thus their diffusion properties report on structural changes in glia, resulting from, for example, inflammation (Ercan, et al, 2016). Creatine and phosphocreatine are present in both tissue types and are tightly linked to cell energetics through the creatine kinase cycle (CK), and it has been shown that increase in energy demand modulates the diffusion coefficient of total creatine (Branzoli, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%